A new species of Breviconia Conroy-Dalton & Huys, 2000 (Copepoda: Harpacticoida: Ancorabolidae Sars) from the Bering Sea, northern Pacific Ocean (Russia) - Garlitska, Lesya; George, Kai Horst; Chertoprud, Elena S. (European Journal of Taxonomy, 2022)
The finding of Breviconia andrei sp. nov. in the Russian Bering Sea enabled the clear-cut phylogenetic characterization of the former monotypic genus Breviconia Conroy-Dalton & Huys, 2000 as a monophylum. Comparison of the new species with B. australis (George, 1998) and other members of the subfamily Ancorabolinae Sars, 1909 yielded four autapomorphies that unambiguously support the monophyletic state of Breviconia: (1) an elongated and approximately 90°-curved mandibular gnathobase, (2) reduction of the maxillar endopod, (3) maxillar endites carrying 2 instead of 3 setae, and (4) loss of the minute seta on the maxillipedal claw. For B. andrei sp. nov., two autapomorphies could be detected, namely, (1) the development of dorsal tubercles on the P5-bearing body somite and (2) the remarkable elongation of the first endopodal segment of the first swimming leg that is twice as long as the whole exopod. Of particular interest is the presence of a 3-segmented endopod in the third swimming leg of the male of B. andrei sp. nov. It disproves the current assumption that the Ancorabolinae are characterized by (among others) the derived presence of an only 2-segmented endopod in the male’s third swimming leg.